-374 T/A RAGE Polymorphism Is Associated with Chronic Kidney Disease Progression in Subjects Affected by Nephrocardiovascular Disease - Baragetti, I.; Norata, Giuseppe; Sarcina, C.; Baragetti, A.; Rastelli, F.; Buzzi, L.; Grigore, L.; Garlaschelli, K.; Pozzi, C.; Catapano, A. (Public Library of Science, 2013)
Background: Chronic kidney disease (CKD) patients present elevated advanced glycation end products (AGEs) blood levels. AGEs promote inflammation through binding to their receptor (RAGE), located on the membrane of mesangial cells, endothelial cells and macrophages. Several genetic polymorphisms influence RAGE transcription, expression and activity, including the substitution of a thymine with an adenine (T/A) in the position -374 of the gene promoter of RAGE. Our study investigates the role of -374 T/A RAGE polymorphism in CKD progression in subjects affected by nephrocardiovascular disease. Methods: 174 patients (119 males (68.4%) mean age 67.2±0.88 years; 55 females (31.6%): mean age 65.4±1.50 years) affected by mild to moderate nephrocardiovascular CKD were studied. Each subject was prospectively followed for 84 months, every 6-9 months. The primary endpoint of the study was a rise of serum creatinine concentrations above 50% of basal values or end stage renal disease. Results: Carriers of the A/A and T/A genotype presented higher plasma levels of interleukin 6 (A/A 29.5±15.83; T/A 30.0±7.89, vs T/T 12.3±5.04 p = 0.01 for both) and Macrophages chemoattractant protein 1 (A/A 347.1±39.87; T/A 411.8±48.41, vs T/T 293.5±36.20, p = 0.04 for both) than T/T subjects. Carriers of the A allele presented a faster CKD progression than wild type patients (Log-Rank test: Chi square = 6.84, p = 0,03) Cox regression showed that -374 T/A RAGE polymorphism (p = 0.037), albuminuria (p = 0.01) and LDL cholesterol (p = 0.038) were directly associated with CKD progression. HDL cholesterol (p = 0.022) and BMI (p = 0.04) were inversely related to it. No relationship was found between circulating RAGE and renal function decline. Conclusions: -374 T/A RAGE polymorphism could be associated with CKD progression and inflammation. Further studies should confirm this finding and address whether inhibiting RAGE downstream signalling would be beneficial for CKD progression. © 2013 Baragetti et al.